Informal Chair Support Groups: Benefits and Obstacles - Emily Detmer-Goebel (Academic Chairpersons Conference Proceedings, 2016)
Support Groups for Chairs can be a beneficial way in which to develop as an academic leader and possibly make the job of chairperson more enjoyable and successful. The roundtable discussion will guide members through a discussion the benefits of forming such an informal support group, but also consider the obstacles.
Keywords: Mentoring; support; job satisfaction; cross-disciplinary; collaboration